The Effectiveness of Transformational Leadership in National and International Non-Governmental Organizations (NGOs) in Yangon - Elizabeth Furio Perez; Yoon Thit Sar; Ma. Teresa S. Buenavista; Leonardo Thenov; James Ahkhi Gwa; Sanjaya Mulya Waani (Journal of Strategic Innovation and Business Management, 2025)
This study focuses into the organizational effectiveness and leadership dynamics of national andinternational non-governmental organizations (NGOs) based in Yangon. Myanmar. The study's objectivesinclude profiling NGO leaders, evaluating transformational leadership styles, and assessing organizationaleffectiveness. A quantitative research strategy is employed, with a structured questionnaire surveydistributed to professionals in the NGO sector. The findings reveal a balanced leadership demographic witha slight predominance of younger leaders, higher levels of educational attainment, and a typicalhierarchical structure. Leadership tenure is diverse, reflecting both short-term and long-term serviceamong leaders. Although leadership and management training are common, a notable proportion ofleaders lack formal training, indicating opportunities for enhanced professional development. Overall,performance metrics such as employee morale, motivation, and leadership effectiveness are rated assatisfactory, with age differences influencing leadership perspectives and organizational outcomes. Theseinsights highlight the importance of tailored transformational leadership strategies to address specificneeds within the sector.